Role of Z-pinches in magnetic reconnection in space plasmas. (8th September 2014) - Olshevsky, Vyacheslav; Lapenta, Giovanni; Markidis, Stefano; Divin, Andrey
Abstract : A widely accepted scenario of magnetic reconnection in collisionless space plasmas is the breakage of magnetic field lines in X-points. In laboratory, reconnection is commonly studied in pinches, current channels embedded into twisted magnetic fields. No model of magnetic reconnection in space plasmas considers both null-points and pinches as peers. We have performed a particle-in-cell simulation of magnetic reconnection in a three-dimensional configuration where null-points are present initially, and Z-pinches are formed during the simulation along the lines of spiral null-points. The non-spiral null-points are more stable than spiral ones, and no substantial energy dissipation is associated with them. On the contrary, turbulent magnetic reconnection in the pinches causes the magnetic energy to decay at a rate of ~1.5% per ion gyro period. Dissipation in similar structures is a likely scenario in space plasmas with large fraction of spiral null-points.